EIF Business Angels Survey 2019: Market sentiment, public intervention and EIF's value added - Helmut Kraemer-Eis; Antonia Botsari; Julien Brault; Frank Lang (European Investment Fund (EIF), 2019)
This working paper presents results of the first EIF Business Angels Survey, a survey among Business Angels (BA) who benefited from the European Angels Fund (EAF), an initiative advised by the EIF and providing equity to BAs for the financing of innovative companies in the form of co-investments. The study provides a detailed overview of the respondents' state of business and market activity as well as their general perception of the European BA market and the required public intervention. In doing so, it looks at the current situation, developments in the recent past and expectations for the future. Furthermore, the study provides detailed insights into the BAs' perception of the value added of the EIF's activities under the EAF, including its impact on the BAs' investment strategy, deal flow, network and reputation, as well as the overall EAF added value. The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by EIF's Research & Market Analysis and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330